In vitro removal of paraquat and diquat from aqueous media using raw and calcined basil seed. Issue 7 (July 2021) - Uematsu, Yugo; Ogata, Fumihiko; Nagai, Noriaki; Saenjum, Chalermpong; Nakamura, Takehiro; Kawasaki, Naohito
Abstract: Raw and calcined basil seeds (BS and BS1000, respectively) were evaluated for their ability to remove herbicides such as paraquat and diquat. The physicochemical properties of BS and BS1000 were determined and the effects of contact time and initial concentration on paraquat and diquat adsorption were assessed. After calcination treatment, the number of pores in BS increased, and the specific surface area was increased from 0.265 to 86.902 m 2 g −1 . The quantity of herbicides adsorbed using BS1000 was greater than that using either BS or medicinal-grade carbon. Additionally, the adsorption quantity increased with the increase in contact time and initial concentration of herbicide. Therefore, BS1000 is a potential resource for the removal of herbicides. Moreover, BS and BS1000 exhibited the capacity for herbicide adsorption in simulated intestinal fluid. Highlights: Calcined basil seed (BS1000) showed the adsorption capability of herbicides. Binding energy of carbon onto BS1000 surface increased after adsorption. Herbicides were removed using BS1000 from simulated intestinal fluid. Abstract : Basil seed, Paraquat, Diquat, Adsorption